IMPLEMENTASI LOGIKA FUZZY METODE MAMDANI BERBASIS WEBSITE UNTUK MENDETEKSI PENYAKIT DIABETES (STUDI KASUS PUSKESMAS) - hayyuni, fatanabila (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
700 million cases by 2045. In Indonesia, diabetes patients are estimated to increase from 10.8 million in 2020 to 16.7 million by 2045. This research develops an early diabetes detection system using Mamdani fuzzy logic method through a web-based platform to support early screening at Community Health Centers.The system analyzes medical parameters including blood glucose levels, blood pressure, body mass index (BMI), and family history using Python with Django framework and SQLite3 database. Testing was conducted through black box testing for system functionality and white box testing for internal code structure analysis. User acceptance evaluation used Likert scale questionnaires with 20 respondents.Results demonstrate the system effectively analyzes health parameters and provides diabetes risk level diagnosis resembling medical decision-making patterns. Functionality testing shows all features operate according to specifications. User evaluation achieved 69.3% score in "Agree" category, indicating the system can assist medical personnel in early diabetes screening at Community Health Centers with good accuracy and user-friendly interface.Keywords: Diabetes, Fuzzy Logic, Mamdani Method, Early Detection, Health Information System